Accessories in clear aligner therapy: Laypeople's expectations for comfort and satisfaction - Jussimar Scheffer Castilhos; Gil Guilherme Gasparello; Sergio Luiz Mota-Júnior; Giovani Ceron Hartmann; Luiz Fernando Iyda Miyagusuku; Matheus Melo Pithon; Orlando Motohiro Tanaka (Tabriz University of Medical Sciences, 2024)
Background. This study explored the layperson's perception of comfort, satisfaction, and willingness to use various accessories in clear aligner therapy. Methods. A total of 267 people analyzed standardized intraoral photographs of a female model in orthodontic treatment using: 1) only clear aligner (CA), the control group; 2) clear aligner+attachments (AT); 3) clear aligners+Cl II elastics (EL); 4) clear aligner+hybrid treatment with esthetic braces (HEB); 5) Clear aligner+hybrid treatment with metallic braces (HMB); 6) clear aligner+mini-implants (MI); 7) clear aligner+mini-implants and elastics for intrusion (MIE). In addition, a social media questionnaire was distributed to assess the willingness to undergo orthodontic treatment with various accessories. Results. There was a significant difference between CA and all the other groups (P<0.001), with CA being considered more comfortable and providing greater satisfaction compared to other accessories. Moreover, AT showed a significant difference in reducing treatment time compared to other groups. Conclusion. The CA was the most comfortable, exhibiting a higher satisfaction rate and a greater willingness to use it. The AT therapy was perceived as more comfortable and was associated with higher satisfaction and a greater likelihood of use, especially if it resulted in reduced treatment time. On the other hand, the participants reported that the HMB, MI, and MIE accessories were less comfortable.